2018
DOI: 10.1186/s12877-018-0822-3
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of LifeFul, a relationship and reablement-focused culture change program in residential aged care

Abstract: BackgroundThe protective, custodial, task-oriented care provided in residential aged care facilitates decreases health and wellbeing of residents. The aim of the study was to conduct a feasibility study of LifeFul – a 12 month reablement program in residential aged care.MethodsLifeFul was developed based on systematic reviews of reablement and staff behaviour change in residential aged care, and in consultation with aged care providers, consumers and clinicians. LifeFul includes: engaging and supporting facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Based on the framework of Medical Research Council guidance, any problems that undermine the feasibility of the evaluation process should be addressed [ 29 ]. Previous studies have reported that participant recruitment, retention, acceptability, and compliance, as well as the expected sample size for predicting the study outcomes through pilot tests, need to interpret carefully [ 30 ]. Although the present study showed it is feasible to assess LTCRL among home care workers in Taiwan, we suggest that future studies should be interpreted carefully, and we present our findings with caution in terms of the feasibility issues.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the framework of Medical Research Council guidance, any problems that undermine the feasibility of the evaluation process should be addressed [ 29 ]. Previous studies have reported that participant recruitment, retention, acceptability, and compliance, as well as the expected sample size for predicting the study outcomes through pilot tests, need to interpret carefully [ 30 ]. Although the present study showed it is feasible to assess LTCRL among home care workers in Taiwan, we suggest that future studies should be interpreted carefully, and we present our findings with caution in terms of the feasibility issues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that nursing homes in America have implemented restorative care programs to meet mandates and receive additional reimbursement [9,37]. A survey in the US showed that the most common restorative care activities were walking, passive and active range of motion, and dressing/grooming [9], which were primarily focused on physical and daily function; engagement with social and recreational activities to improve quality of life has not been emphasized [38].…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the possibility of misunderstanding, the strategy of treating family members as part of the community rather than visitors can contribute to stabilizing residents in the whole program has been suggested [38]. Also, in goal-oriented intervention, such as restorative care, the involvement of informal caregivers can help to set a realistic and achievable goal [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A trend towards developing better collaboration is evident in a paper about the feasibility of LifeFul, a relationship and reablement-focused "culture change program" in residential aged care (Low et al, 2018). However, the authors stated that one of the main challenges to successfully implementing reablement has been compliance by staff.…”
mentioning
confidence: 99%